2021
DOI: 10.3390/agronomy11020300
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Response of Pasture Brome (Bromus valdivianus Phil.) to Defoliation Frequency under Two Soil-Water Restriction Levels

Abstract: Pasture brome (Bromus valdivianus Phil.) has the potential to increase current levels of herbage production and pasture persistence in New Zealand dryland, well-drained soils. However, there is little literature on the effect of defoliation management on growth of this grass under contrasting soil-water restriction levels. The growth physiology and performance of pasture brome were evaluated in pots in a glasshouse. Defoliation frequency (DF) treatments were applied based on three different accumulated growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 22 publications
1
14
1
1
Order By: Relevance
“…In addition, the second residual leaf was counted (second leaf from bottom to top, with values of 0.5 or 0.75 according to its length), to capture its continued growth after a grazing event. Thus, Bv tillers at 3.5–4.0 LS had at least 5 leaves, one residual from the previous grazing cycle, at least one or two fully expanded and three growing (García‐Favre et al, 2021; Ordóñez et al, 2021). Therefore, the LS regrowth of Bv can be based on up to 6 live leaves; meanwhile, Lp LS regrowth can be based on 3 live leaves.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the second residual leaf was counted (second leaf from bottom to top, with values of 0.5 or 0.75 according to its length), to capture its continued growth after a grazing event. Thus, Bv tillers at 3.5–4.0 LS had at least 5 leaves, one residual from the previous grazing cycle, at least one or two fully expanded and three growing (García‐Favre et al, 2021; Ordóñez et al, 2021). Therefore, the LS regrowth of Bv can be based on up to 6 live leaves; meanwhile, Lp LS regrowth can be based on 3 live leaves.…”
Section: Methodsmentioning
confidence: 99%
“…This effect, along with the senescence of the first fully expanded leaf as regrowth progresses (coinciding with a decline in pasture quality), determines an optimum range of LS recommended for grazing (Fulkerson & Donaghy, 2001). It was shown that the optimum LS for production and persistence of Lp lies between 2 and 3.0 leaves/tiller (Fulkerson & Donaghy, 2001), while for Bv, it is between 3.5 and 4.0 leaves/tiller (García‐Favre et al, 2021; Ordóñez et al, 2021). In a mixture, to achieve a good pasture production and persistence, both species should be defoliated close to their optimum LS.…”
Section: Introductionmentioning
confidence: 99%
“…In the current experiment, several factors related to pasture availability (pre-and post-grazing herbage mass) and quality in terms of nitrogen (CP) were similar between Bv and Lp, suggesting that Bv could be used to replace Lp, especially for the months of the year where the water deficit is increased. Bromus valdivianus is a native grass species from Southern Chile that is characterized by its high DM yield and good forage quality, even under restricted conditions of soil water content [40][41][42], which is related to its deep root system, which enables capture of water from deeper soil strata, increasing its drought tolerance [18][19][20]. It was observed that ADF and NDF content were greater for Bv, while WSC content was greater for Lp.…”
Section: Chemical Composition Of Pasture and Herbage Massmentioning
confidence: 99%
“…Bromus valdivianus is a native species from the humid temperate region of Chile characterized by a high tolerance to restricted conditions of soil water (dry periods), mainly related to its deep root system, allowing for water from lower soil strata to be obtained [18,19]. Additionally, Bv is characterized by a high pasture availability, being similar to Lp, the most common grass species used for pasture-based dairy systems, and therefore has the potential to increase current levels of herbage production and pasture persistence in drylands [20]. Moreover, Bv shows a high content of protein (~19% CP) and fiber (~48% NDF) and a medium content of energy (2.5 Mcal ME/kg DM) [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation